The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/frph.2021.700850
|View full text |Cite
|
Sign up to set email alerts
|

Coping Mechanisms of Previously Diagnosed and New HIV-Discordant, Heterosexual Couples Enrolled in a Pilot HIV Self-Testing Intervention Trial in Central Uganda

Abstract: Introduction: Learning that a couple has HIV-discordant results can create tensions in the relationship including separation. We explored the coping mechanisms of HIV-discordant, heterosexual couples enrolled in an HIV self-testing (HIVST) intervention trial in Central Uganda.Materials and Methods: This qualitative study was nested within a pilot HIVST intervention trial targeting pregnant women and their male partners in central Uganda. In-depth interviews were conducted with 18 individuals from 13 HIV-discor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(35 reference statements)
2
0
0
Order By: Relevance
“…This support followed selective disclosure on HIV status by study participants. These findings concur with those of a study by Matovu et al ( 2021 ), in Uganda indicating that the serodiscordant couples usually seek support from health workers, friends and relatives. Related to this, Dessalegn et al ( 2019 ) in a study in Ethiopia, found that HIV disclosure for individual in serodiscordant relationships was sometimes delayed, with the likelihood for onward transmission.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This support followed selective disclosure on HIV status by study participants. These findings concur with those of a study by Matovu et al ( 2021 ), in Uganda indicating that the serodiscordant couples usually seek support from health workers, friends and relatives. Related to this, Dessalegn et al ( 2019 ) in a study in Ethiopia, found that HIV disclosure for individual in serodiscordant relationships was sometimes delayed, with the likelihood for onward transmission.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of support structures has a negative impact on the health of HIV serodiscordant couples since they are exposed to high-risk behaviour as partners. Similar results were obtained by Matovu et al ( 2021 ), who found that HIV-negative partners in discordant relationships are at risk of HIV infection. Pedrosa et al ( 2016 ) postulate that for couples in HIV serodiscordant relationships, the main sources of social support were from friends and family.…”
Section: Introductionsupporting
confidence: 90%